Training Children's Character Education Through Technology-based Learning Media - Tazkya Nayla Kuntadi; Fakhri Dhiya Hidayat (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
Education is defined as a form of mentoring and developing the potential of students who are directed and embedded in personality, then can be applied in everyday life. Character literally comes from the Latin character, which means, among other things: character, character, psychological traits, character, personality or morals. Someone who behaves dishonestly, is cruel, likes to steal, is said to be a person with bad character. Meanwhile, someone who likes to be honest, helpful, polite, can be said to be someone who has good character. So, the term character is more reflected in a person's personality. Lickona states that character education is a deliberate effort to help someone so that he can understand, pay attention to and carry out core ethical values.